Perbedaan Penerapan Problem Based Learning Dan SaranaBelajar Terhadap Kemampuan Berpikir Kritis SiswaPada Mata Pelajaran Ips Ekonomi Kelas VIII DiSMP Al Muayyad Surakarta Tahun Ajaran 2015/2016 - Astuti, Noviana, Dr. Djalal Fuadi, M.M (2016)
The purpose of this study to describe and analyze: (1) differences implementation of Problem Based Learning and application without the Problem Based Learning of the critical thinking skills of students, (2) differences in the means of learning the critical thinking skills of students, (3) the interaction of the application of learning models and learning tools the students' critical thinking skills. Research methods. This research is a quasi-experimental design experiment. The study population was all class VIII SMP Al Muayyad Surakarta. The study sample consisted of two classes. The sampling technique using cluster random sampling. The data collection instruments such as questionnaires, tests, and documentation. Testing studies using testing requirements analysis and hypothesis testing. Test requirements analysis consists of a balance test, test for normality and homogeneity test. Testing the hypothesis with Two Way Anova test. The results showed that the use Two Way ANOVA test is obtained: (1) there is differences implementation of Problem Based Learning and Problem Based Learning application without the critical thinking skills of students, with F count = 8.561 > F table = 4.04. On average marginal value of critical thinking skills experimental class of 56.260 while the control group had an average marginal critical thinking skills at 50.946. (2) There is a learning tool to students' critical thinking skills, with F count = 4.281 > F table = 3.19. Based on the average marginal good learning tool at 56.613 results critical thinking skills that better than 54.187 learning tool that is enough. Students who have a good learning tool provides results of critical thinking skills that better than learning means less is 50.008. (3) there is no interaction of the application Problem Based Learning and learning facilities to students' critical thinking skills, with F count = 3.111 < F table = 3.19. So the differences between the model Problem Based Learning and the conventional model for any means of learning to follow the marginal mean comparisons.